Early-Life Sleep Deprivation Enhanced Alcohol Consumption in Adolescent Rats - Atrooz, Fatin; Alrousan, Ghalya; Hassan, Arham; Salim, Samina (Frontiers in Neuroscience, 2022)
Evidence in the literature suggests that sleep deprivation during early life developmental stages, by impacting important processes such as the reward circuit maturation, may increase the vulnerability for alcohol and substance use. The mechanisms involved are not fully understood. In this study, utilizing our previously established model, we examined the impact of early life sleep deprivation on alcohol consumption in adolescent rats. Male Sprague Dawley rats served either as control (CON) or sleep deprived (SD). Sleep deprivation was induced using Pinnacle automated sleep deprivation apparatus. SD group of rats were sleep deprived for 6-8 hours per day for 14 days from postnatal day (PND)19-PND32. At PND33, anxiety- and depression-like behavior were assessed in rats using elevated plus maze and sucrose splash test, respectively, At PND39, alcohol consumption was assessed in rats for 5 consecutive days using the two-bottle choice paradigm, water versus 5% ethanol. SD rats exhibited significant anxiety- and depression-like behavior as compared to CON rats. Interestingly, SD rats consumed larger volume of alcohol when compared to CON rats which was significantly higher at day 5 (Mean of alcohol consumption (ml) ± StD; CON= 6.67± 3.42; SD =19.00 ± 6.05, p = 0.0126). SD rats also showed high preference for alcohol over water which was significantly higher at day 5 (Mean of alcohol preference (%) ± StD; CON= 26.85 ± 14.97; SD = 57.69 ± 5.61, p = 0.014). Our data suggest that early life sleep deprivation enhanced alcohol consumption in adolescent rats.